2006
DOI: 10.1073/pnas.0604607103
|View full text |Cite
|
Sign up to set email alerts
|

WNK1 and OSR1 regulate the Na + , K + , 2Cl cotransporter in HeLa cells

Abstract: Oxidative stress-responsive kinase (OSR) 1 and sterile20-related, proline-, alanine-rich kinase (SPAK) are Ste20p-related protein kinases that bind to the sodium, potassium, two chloride cotransporter, NKCC. Here we present evidence that the protein kinase with no lysine [K] (WNK) 1 regulates OSR1, SPAK, and NKCC activities. OSR1 exists in a complex with WNK1 in cells, is activated by recombinant WNK1 in vitro, and is phosphorylated in a WNK1-dependent manner in cells. Depletion of WNK1 from HeLa cells by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
162
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(182 citation statements)
references
References 41 publications
16
162
0
Order By: Relevance
“…Through their effects on SPAK/OSR1, WNK kinases control members of the SLC12 family of Cl − /cation cotransporters (NKCCs, KCCs, NCC) and thereby play a pivotal role in cellular Cl − homeostasis (39). Recent studies have revealed that WNK1 and WNK4 phosphorylate OSR1 and SPAK (40)(41)(42)(43) and thereby promote phosphorylation and activation of NKCC1. Our data show that all four kinases, SPAK, OSR1, WNK1, and WNK4, are expressed in ORN cilia, and SPAK and OSR1 are both necessary for maximal activation of the transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Through their effects on SPAK/OSR1, WNK kinases control members of the SLC12 family of Cl − /cation cotransporters (NKCCs, KCCs, NCC) and thereby play a pivotal role in cellular Cl − homeostasis (39). Recent studies have revealed that WNK1 and WNK4 phosphorylate OSR1 and SPAK (40)(41)(42)(43) and thereby promote phosphorylation and activation of NKCC1. Our data show that all four kinases, SPAK, OSR1, WNK1, and WNK4, are expressed in ORN cilia, and SPAK and OSR1 are both necessary for maximal activation of the transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertonicity stimulates autophosphorylation of WNK1 on serine-382, activating WNK1 to phosphorylate SPAK and OSR1 (Anselmo et al, 2006;Zagorska et al, 2007). SPAK and OSR1 kinase activate NKCC1 and NKCC2 by causing phosphorylation on the transporters (Moriguchi et al, 2005;Vitari et al, 2005Vitari et al, , 2006Anselmo et al, 2006). Hyperotonicity also induces a rapid redistribution of WNK1 from cytosol to vesicular structures (Zagorska et al, 2007).…”
Section: Upstream Regulators Of Wnk Kinasesmentioning
confidence: 99%
“…In addition to the regulation of NCC as described above, WNK1, 3 and 4 increase ion transport mediated by NKCC1 and NKCC2 (Rinehart et al, 2005;Vitari et al, 2005;Anselmo et al, 2006;Gagnon et al, 2006). WNK3 and 4 also inhibit KCCs (Vitari et al, 2005;Gagnon et al, 2006;Garzon-Muvdi et al, 2007).…”
Section: Regulation Of Slc12 Cation-chloride Cotransporters By Wnksmentioning
confidence: 99%
See 2 more Smart Citations